Can pediatric rheumatologists apply available hip scoring systems in daily practice for juvenile idiopathic arthritis? - Maatallah, Kaouther; Lassoued Ferjani, Hanene; Ben Nessib, Dorra; Dghaies, Abir; Kharrat, Lobna; Majdoub, Fatma; Kaffel, Dhia; Hamdi, Wafa (Frontiers in Pediatrics, 2025)
IntroductionScoring systems for hip involvement in juvenile idiopathic arthritis exist, however, they were not used in daily practice, and their reproducibility was not proven.ObjectivesWe aimed to determine the applicability, reliability, and repeatability of the two scoring systems of the hip in juvenile idiopathic arthritis patients.MethodsTwo expert pediatrics rheumatologists analyzed pelvic radiographs from 25 children with JIA hip involvement. We scored the findings according to two previous valid scoring systems (The childhood Arthritis Radiographic Score of the Hip and the newly developed score proposed by the project Health-e-Child) at baseline and after three weeks. We used kappa statistics to rate inter- and intra-observer variability.ResultsThe joint space narrowing, erosion, and growth abnormalities had moderate to good reliability when the first score was used. However, the subchondral cysts, malalignment, and sclerosis have poor concordance in the two observers. For the second score, the intraclass correlation coefficient (ICC) was high in only one reader for head erosion (κ = 0.833 vs. κ = 0.308; p < 0.001), enlarged fovea (κ = 0.279 vs. κ = 0.907; p < 0.05), and growth abnormalities (κ = 0.823 vs. κ = 0; p < 0.001; p = 0.5). Therefore, the intra-reader agreement for head femoral measuring and centrum–column–diaphysis angle showed good reliability for only one reader. Training has only improved the observers' agreement with the assessment of growth disorders in the first score. The interpretation agreement was also increased compared to the baseline in the femoral measurements.ConclusionThe reliability of these tools seemed to be lower without electronic measurements and the pediatric rheumatologists needed more training before applying these scoring in the practice hip monitoring. Clinical Trial RegistrationNCT05206968 Last Update: 01/12/2022.